2000
DOI: 10.1080/014434100110371
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Relationship Between Teacher Motivation and Pupil Motivation

Abstract: This article reports the ® ndings of a small scale investigation in the form of a blind study carried out in four schools in the north east of England. It concerns the relationship between teacher motivation (n 5 4) and pupil motivation (n 5 66) during pupils' participation in design and technology project work at Key Stage 4. It was recognised that the sample of teachers was too small to be considered representative of motivated and demotivated design and technology teachers in general terms. However, the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 6 publications
5
57
0
17
Order By: Relevance
“…This importance can be explained to teachers in terms of professional development and needs (Deci & Ryan, 2000). Because of its relation and usefulness to them, teachers are more likely to be motivated to make changes that could influence student achievement, as Atkinson (2000) explained that teacher motivation is important for students' learning. Eccles et al (1983) proposed that there are clear causal links between individuals' goals, ability beliefs, subjective values, and expectancies for success (p. 81).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This importance can be explained to teachers in terms of professional development and needs (Deci & Ryan, 2000). Because of its relation and usefulness to them, teachers are more likely to be motivated to make changes that could influence student achievement, as Atkinson (2000) explained that teacher motivation is important for students' learning. Eccles et al (1983) proposed that there are clear causal links between individuals' goals, ability beliefs, subjective values, and expectancies for success (p. 81).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In particular, teacher motivation is a growing research area in recent years because previous research has revealed that teacher motivation plays an important role in student learning (Atkinson, 2000). The recent research on teacher motivation focuses on the career choices of pre-service teachers.…”
mentioning
confidence: 99%
“…The teachers' assessment is mediated by two variables: (1) the student's intelligence, that is, the greater the intelligence, the better the academic results and the better reciprocal appreciation between teacher and student; (2) family support for study also makes the student value his teacher more highly (Castejón and Pérez, 1998). Other studies find positive relationships between the teacher's motivation and that of the student (Atkinson, 2000). Teacher-pupil relations are also mediated by the teacher's attribution of poor performance to the student (Georgiou et al, 2002).…”
Section: Introductionmentioning
confidence: 95%
“…Students' motivation is positively affected by technology and teachers' motivation (Atkinson, 2000). Teachers should make conscious efforts to create activities that encompass some form of technological tool due to students' positive response to technology and motivation created by technology for them.…”
Section: Technology and Its Effect On Motivation And Retentionmentioning
confidence: 99%